cos(x)+cos(7x)-cos(4x)=0

Simple and best practice solution for cos(x)+cos(7x)-cos(4x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for cos(x)+cos(7x)-cos(4x)=0 equation:


Simplifying
cos(x) + cos(7x) + -1cos(4x) = 0

Multiply cos * x
cosx + cos(7x) + -1cos(4x) = 0

Remove parenthesis around (7x)
cosx + cos * 7x + -1cos(4x) = 0

Reorder the terms for easier multiplication:
cosx + 7cos * x + -1cos(4x) = 0

Multiply cos * x
cosx + 7cosx + -1cos(4x) = 0

Remove parenthesis around (4x)
cosx + 7cosx + -1cos * 4x = 0

Reorder the terms for easier multiplication:
cosx + 7cosx + -1 * 4cos * x = 0

Multiply -1 * 4
cosx + 7cosx + -4cos * x = 0

Multiply cos * x
cosx + 7cosx + -4cosx = 0

Combine like terms: cosx + 7cosx = 8cosx
8cosx + -4cosx = 0

Combine like terms: 8cosx + -4cosx = 4cosx
4cosx = 0

Solving
4cosx = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Divide each side by '4'.
cosx = 0

Simplifying
cosx = 0

The solution to this equation could not be determined.

See similar equations:

| (3t+2q)(7t-9q)= | | u+25=-61 | | 5r^2-55r+15=0 | | cos(x)+cox(7x)-cox(4x)=0 | | 89=n+3 | | 15y^3+12y^2+6y= | | 2+0.3y=11 | | 2(7x+5)=3(3x-2) | | 9(m)=25(m)+22 | | 6m+14m=-16 | | 6b^2=-18b | | 21=2p-9 | | 40+3x+20-5x=30 | | G+2g+6=6g-21 | | 20x-27=73 | | 5(z)+8=4(z)+20 | | 1.3x+3=-1 | | -6x+9y=84 | | 2w-21.5=9 | | 2x-3y=-28 | | 40-4x=2-10 | | -24y^3-64y^2=0 | | (Y^2+3)(y^2-12)=0 | | 7(x-2)=4(x+5) | | 7x-28=6x-1 | | 3(X+4)+7X=4 | | 8+3b=2(9-b) | | 2f+700=-74 | | -10p+9p=13 | | (x-10)(x+2)= | | k(k-1)-30=0 | | 20+18k=956 |

Equations solver categories